Coordinating participation in dialogue interpreting - Baraldi, Claudio; Gavioli, Laura (Benjamins translation library., 2012)
Interpreters' reflexive coordination may promote different forms of mediation. Dialogic mediation, in particular, achieves promotion of active participation, displays sensitivity for the interlocutors' interests and/or needs, and treats alternative perspectives as reciprocal enrichment. Drawing on a set of healthcare interactions involving Arabic-speaking patients in Italian services, this chapter discusses interpreting actions of mediators included in sequences of dialogic mediation, in particular: (1) promotional questions, which encourage the production of personal narratives and narratives.